Evaluasi Penerapan Manajemen Risiko Berbasis ISO 31000 untuk Mengelola Risiko Operasional dalam Kegiatan Pelayanan Jasa pada PT SMTK di Surabaya - Feliana Novita Sari; Senny Harindahyani (CALYPTRA, 2018)
Every company always strives to achieve goals. In achieving that goal, all companies will certainly face a risk that can hinder the company to achieve its goals. To achieve the objectives, the company must be able to manage the risks which can hamper their operational activities that will impact in achieving company goals. Risk management can be soved with risk management. By applying risk management, it will assist the company to improving control and improving the effectiveness and efficiency of operational activities. The purpose of this study is to analyze and evaluate risk management based on ISO 31000 to manage the risks, especially operational risks that occur in transportation companies. The results of this research at PT SMTK in Surabaya indicate that the risk management has been run has fulfilled the framework and stages of risk management based on ISO 31000. Evaluation of risk management can help PT SMTK to improve the deficiencies in the process of risk management and internal control. Thus PT SMTK can obtain recommendation as a consideration for more effective process of risk management improvement.